THE MAIN DIRECTIONS FOR IMPROVING THE EFFICIENCY AND COMPETITIVENESS OF THE AGRICULTURAL SECTOR (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This article explores the causes of obstacles to improving the efficiency and competitiveness of the agricultural sector today. Defines the main directions for increasing the yield of agricultural products. Also, productivity in the field determines the perspective of society in socio-economic life.